Stiffness, pain, and joint counts in chronic chikungunya disease: relevance to disability and quality of life - Watson, Hugh (Clin Rheumatol, 2020)
INTRODUCTION/OBJECTIVES: To characterize the importance of musculoskeletal stiffness in a cohort of chikungunya patients with chronic joint symptoms. METHOD: Eighty-two patients were followed up 3 years after chikungunya infection. Tender and swollen joint counts, a pain intensity scale, Health Assessment Questionnaire-Disability Index (HAQ-DI), and the EuroQol EQ-5D quality of life instrument were completed. A musculoskeletal stiffness questionnaire provided scores for overall stiffness and its components: stiffness severity, physical impact, and psychosocial impact. RESULTS: Patients had a mean age 51 ± 14 years. Sixty-seven patients were still experiencing chronic arthralgia. Musculoskeletal stiffness was reported by 43/67 patients with arthralgia and 3/15 patients without arthralgia. A physical impact of stiffness was reported by 87% patients and psychosocial impact by 71% patients. Mean tender joint count in patients reporting arthralgia was 6 ± 7, mean pain intensity 65 ± 20 out of 100, mean HAQ-DI was 0.54 ± 0.52, and mean EQ-VAS global health perception was 68 ± 62 out of 100. Stiffness severity was correlated with tender joint counts (ρ = 0.46) and pain intensity (ρ = 0.40). All three measures were equally well correlated with the EuroQol-VAS global health perception. Pain and tender joints were better correlated with the HAQ-DI (ρ = 0.68 and ρ = 0.63), but stiffness was more strongly correlated with several quality of life domains, including mobility. Swollen joints were a poor predictor of outcomes. CONCLUSIONS: Musculoskeletal stiffness following chikungunya infection is distinct from arthralgia. It does not always occur in the same patients or with a corresponding intensity. Joint pain and stiffness may be independently associated with disability and quality of life assessments.